Faktor Risiko Masalah Gizi Kurang pada Balita di Indonesia - Annisa Nuradhiani (CV. ALIM'SPUBLISHING, 2023)
One of the most common health problems among toddlers in Indonesia is malnutrition. Based on the results of the 2018 Riskesdas, nationally the prevalence of malnutrition is 13.8%. This study aims to determine the risk factors associated with the incidence of malnutrition in toddlers in Indonesia. The research method used is through searching articles on Google Scholar during the period of 2018-2021 using the keywords toddlers malnutrition, underweight in toddlers, factors of under nutrition in toddlers, and determinants of toddlers malnutrition. As the results, the study found 5 journal articles mentioned the risk factors of malnutrition in toddlers, which are direct factors and indirect factors. The direct factors of malnutrition in toddlers are : infectious diseases and poor parenting patterns, while the indirect factors are : not being provided exclusive breastfeeding, low quality of mother's knowledge regarding feeding toddlers, low economic status and family food security, the short gap of giving birth, and inadequate personal hygiene as well as environmental sanitation.